Political Theology the “Modern Way” - Retallick, Shaun, author.
1 online resource (288 pages)
Keywords: In Political Theology the “Modern Way“: The Case of Jacques Almain (d. 1515) , Shaun Retallick provides the first monograph on this late medieval philosopher-theologian and conciliarist, and his thought. He demonstrates that Almain's political theology, of which ecclesiology is a sub-discipline, is strongly impacted by the Via moderna . At the heart of his political theology is the individual and his or her will. Yet, the individual is rarely viewed in isolation from others; there is a strong emphasis on community and on the religious and secular bodies through which it is realized. But these bodies, including the Church, are understood in collectivist rather than corporatist terms, which tends to a quite radical form of conciliarism.